Portfolio choice with house value misperception - Stefano Corradin; José Luis Fillat Comenge; Carles Vergara-Alert (Federal Reserve Bank of Boston, 2017)
Households systematically overvalue or undervalue their houses. We compute house value misperception as the difference between self-reported and market house values. Misperception is sizable, countercyclical, and persistent. We find that a 1 percent increase in house overvaluation results, on average, in a 4.56 percent decrease in the share of risky stock holdings for those households that participate in the stock market. We then build a rational inattention model in which households make decisions based on their perceived level of housing wealth. Numerical simulations generate the effects of house value misperception on the portfolio choices that we observe in the data.
Keywords: G11; D11; D91; R21; C61; 330; portfolio choice; housing; transaction costs; information costs; inaction bands; rational inattention